2011
DOI: 10.1007/s00198-011-1644-8
|View full text |Cite
|
Sign up to set email alerts
|

Bone health in multiple sclerosis

Abstract: People who are disabled with multiple sclerosis (MS) may be at increased risk of osteoporosis. This review discusses issues relevant to bone health in MS and makes practical recommendations regarding prevention and screening for osteoporosis and fracture risk in MS. A search of the literature up until 5 April 2011 was performed using key search terms, and articles pertinent to bone health in MS were analysed. Bone mineral density (BMD) is reduced at the lumbar spine, hip and total body in MS, with the degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 85 publications
2
28
1
1
Order By: Relevance
“…9,17 Similarly, even if the disability level and mineral density relationship have been reported as strongly related to each other, fracture risk is higher in patients with moderate rather than severe disability. 5,41,42 Therefore, reliable correlation between fall status and Expanded Disability Status Scale can be found only at intermediate levels of the scale, but not at the lower and upper extremities. In this regard, clinical 16,18,22,23,24,26,27 or computer-based assessments of balance [21][22][23]27 could be more useful for enhancing our diagnostic ability.…”
Section: Discussionmentioning
confidence: 99%
“…9,17 Similarly, even if the disability level and mineral density relationship have been reported as strongly related to each other, fracture risk is higher in patients with moderate rather than severe disability. 5,41,42 Therefore, reliable correlation between fall status and Expanded Disability Status Scale can be found only at intermediate levels of the scale, but not at the lower and upper extremities. In this regard, clinical 16,18,22,23,24,26,27 or computer-based assessments of balance [21][22][23]27 could be more useful for enhancing our diagnostic ability.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in mobility is strongly associated with osteoporosis aggravation and muscle wasting as well as more frequent falls. Therefore, simply due to a fall, an MS patient may suffer from a major fracture leading to prolonged bed rest and experience further loss of bone density and muscle mass worsening the patients' disability [11].…”
Section: Introductionmentioning
confidence: 99%
“…Fall incidence was reported in 6 studies from 34% to 64% of MS patients with frequencies of two falls in the last 2 months [11]. Falls can cause physical injuries, such as fractures, soft tissue damage, activity restrictions and reduced mobility.…”
Section: Introductionmentioning
confidence: 99%
“…7 Recent studies in the United Kingdom 8 and the Netherlands 9 found that the risk of hip fracture in people with MS was higher than in the general population, and that people with MS with a history of falling had double the risk of osteoporotic fracture. 8 The incidence of falls was significantly greater in people with Supported by Multiple Sclerosis Ireland through the Getting the Balance Right Project.…”
mentioning
confidence: 99%